2016
DOI: 10.1155/2016/9167361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Visual Outcomes of Optic Neuritis in Chinese Children

Abstract: Purpose. Although optic neuritis (ON) in children is relatively common, visual outcomes and factors associated with the condition have not been well documented. The aim of this study was to evaluate the clinical features and visual outcomes of ON in Chinese children. Methods. Patients with a first episode of ON at a tertiary neuroophthalmic centre in China were assessed and followed up for at least three months. Visual outcomes and clinical, laboratory, and neuroimaging findings were reviewed. In patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…In this study, the MOG antibody seropositive pediatric cohorts presented favorable visual outcomes; other studies have also shown similar results in pediatric patients with MOG-ON (Chen et al, 2018;Song et al, 2019;Chen et al, 2018) Furthermore, we found better visual outcomes of MOG-ON in children compared than in adult patients despite similar VA at nadir, which may reflect the greater capacity of remyelination after ON in children (Chen et al, 2018) Many studies have shown dramatic visual recovery after ON in children than in adults (Wan et al, 2014;Zhou et al, 2016) However, these studies did not perform antibody testing or evaluate the etiology of ON, and they were based on heterogeneous etiologies. Therefore, interpretation of these study results is limited.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, the MOG antibody seropositive pediatric cohorts presented favorable visual outcomes; other studies have also shown similar results in pediatric patients with MOG-ON (Chen et al, 2018;Song et al, 2019;Chen et al, 2018) Furthermore, we found better visual outcomes of MOG-ON in children compared than in adult patients despite similar VA at nadir, which may reflect the greater capacity of remyelination after ON in children (Chen et al, 2018) Many studies have shown dramatic visual recovery after ON in children than in adults (Wan et al, 2014;Zhou et al, 2016) However, these studies did not perform antibody testing or evaluate the etiology of ON, and they were based on heterogeneous etiologies. Therefore, interpretation of these study results is limited.…”
Section: Discussionsupporting
confidence: 80%
“…Ocular pain on eye movement and perineural enhancement on MRI was less common in our cohort of pediatric MOG-ON patients than in the adult patients reported in previous studies, (Chen et al, 2018;Zhao et al, 2018) while optic disk swelling was quite common. It is well known that pain with eye movement is less frequent in pediatric ON than in adult ON (Wan et al, 2014;Zhou et al, 2016) These differences between pediatric and adult patients was also observed in our pediatric MOG-ON patients. We also found that perineural enhancement, which is a distinct radiologic feature in adult patients with MOG-ON, was not a distinctive radiologic feature in pediatric patients with MOG-ON.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of serum MOG-Abs has been proposed to indicate a specific subtype of ON, as it is becoming clear that this biomarker is associated with specific disease features and may be a novel serodiagnostic biomarker of demyelination 18. Zhou et al 13 tested the serum of 47 Chinese children patients and determined that among them, 13 (27.7%) were AQP4-Ab-positive; however, MOG-Abs were not tested for in this study. To our knowledge, the present study is the first report on the proportion of paediatric MOG-ON in China.…”
Section: Discussionmentioning
confidence: 76%
“…A meta-analysis on isolated optic neuritis in children aged less than ten years showed that bilateral optic neuritis was more prevalent than unilateral, and vice versa in children over ten years of age 5 . A comparison of the clinical features of optic neuritis from 17 studies among various races around the world also reported by Zhou et al (2016) showed a high rate of recovery of vision (more than 75%) and achieved vision ≥ 20/40 after follow-up ranging from of 1 year to 10 years, and cases of neuritis are more common in girls than boys. In addition, 50% of cases are bilateral and mostly accompanied by optic disc edema.…”
Section: Discussionmentioning
confidence: 74%
“…The study by Zhou on a population of Chinese children also concluded that the patient's age at onset ≤10 years had a significantly better predictive value of vision recovery than older age, and the visual-optic prognosis of neuritis in children was better than in adults. Gender, laterality, initial vision, optic disc edema, MRI images, and therapy did not affect the final visual outcome 6 . Despite the recovery, there may still be subtle changes in their vision.…”
Section: Discussionmentioning
confidence: 78%